Thermodynamical Modelling of a Stratified Charge Spark Ignition Engine - Smith,JK; Roberts,P; Kountouriotis,A; Richardson,D; Aleiferis,P; Ruprecht,D (International Journal of Engine Research, 2020)
Combustion of a charge with spatially and temporally varying equivalence ratio in a spark ignition engine was modelled using the Leeds University Spark Ignition Engine quasi-dimensional thermodynamic code. New sub-models have been integrated into Leeds University Spark Ignition Engine that simulate the effect of burnt gas expansion and turbulent mixing on an initial equivalence ratio distribution. Realistic distribution functions were used to model the radially varying equivalence ratio. The new stratified fuel model was validated against experimental data, showing reasonable agreement for both the pressure trace and percentage heat released. Including the effect of turbulent mixing was found to be important to reproduce the trend in the differences between the stratified and homogeneous simulations.